STRATEGI PEMETAAN KUALITAS SDM DALAM MENUNJANG DESTINASI WISATA DI PULAU TIDUNG, KEPULAUAN SERIBU DI ERA DIGITAL - Franky Franky (KELOLA: Jurnal Ilmiah Manajemen, 2021)
This study aims to provide direction or guidance for a strategy of mapping the quality of human resources to develop the tourist destinations of the Tidung island in the Thousand Islands. Human resources have a central role and responsibility in developing each line of business, including in the tourism sector. The tourism sector demands the fulfillment of the quality of human resources with scientific competence, strategies and skills. This study uses a qualitative method with secondary data sources. Data analysis using descriptive analysis method or library research on several studies. Sources of data were collected through literature studies, statistical reports, discussions, and researcher elaborations. The results of this study are strategies to improve the quality of human resources, which are divided into two elements, namely governance and professional elements. In the governance element, programs are carried out to improve the quality of human resources through the possession of adequate competencies and networking. Whereas the professional element consisting of business owners and staff, tourism management, inclusive management, and certification as well. An English language and using technology skills as added value are developed. If human resources on the island of Tidung are equipped with the above study, then the development of tourist destinations on the island of Tidung, Thousand Islands can be realized optimally.